Persistent drug-associated memories coexist with hippocampal-dependent cognitive decline and altered adult hippocampal neurogenesis in mice withdrawn from cocaine. - Mañas-Padilla, María del Carmen; Gil-Rodríguez, Sara; Sampedro-Piquero, Patricia; Ávila-Gámiz, Fabiola; Rodriguez-de-Fonseca, Fernando; Santín-Núñez, Luis Javier; Castilla-Ortega, María Estela (My University, 2019)
Aims: Using a new animal model (‘chronic’ cocaine-induced conditioned place preference –CPP- paradigm), this work studied whether the long-term maintenance of cocaine-associated memories was concomitant to cognitive impairment and adult hippocampal neurogenesis (AHN) alterations. Methods: Male c57BL/6J mice were submitted to a CPP task treated either with cocaine (20 mg/kg/day) or saline for 14 days (n=10 per group). Bromodeoxyuridine (BrdU) was administered to label the new hippocampal neurons generated one week after the last cocaine dose. After 28 drug-free days, mice were assessed for the CPP memory and on a battery of emotional and cognitive behavioral tests. After completion of behavior, brains were collected for AHN analysis. Results: In mice treated with cocaine, preference for the cocaine-paired compartment (CPP memory) persisted over time. In addition, the cocaine-withdrawn mice overall displayed normal emotional behavior but they showed hippocampal-dependent cognitive impairment for novelty recognition (object and place) and spatial (reference and working) memory. The number of BrdU+ cells was unaffected, suggesting that cocaine withdrawal did not impair basal AHN. However, the cocaine-withdrawn mice excessively increased the number immature hippocampal neurons (doublecortin+) after behavioral training, in direct correlation with their cognitive performance, probably as a result of effortful learning. Conclusions: The CPP memory induced by cocaine remains unaltered after a prolonged period of abstinence, accompanied by defective acquisition of new learnings. Since the doublecortin+ neurons correlated with better cognitive performance in the cocaine-withdrawn mice, strategies that increase AHN could alleviate neurocognitive deficits induced by cocaine.
Keywords: Toxicomanía - Complicaciones y secuelas; Cocaina; Hipocampo (Cerebro); Experimentación animal; Cocaine; Neurogenesis; Cognition